Utilização de revestimento comestível contendo amido e nisina na conservação de salada de frutas minimamente processadas - Couto, Hyrla Grazielle Silva de Araújo (2016)
The aim of this study was to evaluate the action of edible coating the corn starch-based embedded with the bacteriocin nisin in the conservation of fresh cut fruit salad. The salads were composed of mango, papaya and pineapple. After processing the minimum salads were submitted to the following treatments: uncoated fruit salad (control); Corn starch coating without Nisin; and corn starch coating with Nisin. All samples were packed in polyethylene terephthalate (PET) packages for 12 days at 5 ± 1 ° C and 80% RH. At 0, 3, 6, 9,12 physicochemical analysis of soluble solids content were held, pH, titratable acidity, ascorbic acid content, phenolic compounds, carotenoids, color, loss of weight and Polyphenol oxidase activity of enzymes. The microbiological analysis included aerobic mesophilic count, molds and yeasts, and survival analysis of Listeria monocytogenes inoculated in minimally processed fruit salads plus the added edible coating or not nisin. The fruit salads treated with edible coating nisin and showed significantly less mass loss, and increased vitamin C content when compared with control treatment samples. Coated fruits showed also significantly lower levels of soluble solids and lower activity of polyphenol oxidase. There was no significant variation in relation to the analysis of pH, acidity, carotenoids and color among treatments. It was observed increase in mesophilic aerobic count in all samples but, on samples coated with starch and nisin, it was found that the microbial population was statistically lower than the other treatments. Samples of fruit salad coated with corn starch, had significantly lower counts of yeasts and molds until the 6th day of storage. The presence of nisin resulted in significant reduction in the number of viable cells of the bacterium L. monocytogenes inoculated in output of fruit, unchecked behavior in samples of other treatments during the 12 days of storage at 5 ° C. The results of this study demonstrate that the use of corn starch coating and nisin combined with good processing practices and minimum control of storage conditions (temperature and humidity) was effective in preserving minimally processed fruit salads. Once a positive influence on the physical and chemical parameters evaluated, and obtained the best results in relation to maintaining the microbiological quality of salads for up to 12 days.